Ameliorating effect of vitamin C and selenium against nicotine induced oxidative stress and changes of p53 expression in pregnant albino rats (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was aimed to evaluate the effects of daily intake of vitamin C or selenium against deleterious effects of nicotine toxicity on pregnant albino rats.Materials and methods: Forty albino pregnant rats were equally distributed into four groups. Group A was considered as control. Group B was administered with nicotine dosed at 1 mg/kg body weight (bwt) daily for 7 weeks (wks) from 1st day of gestation until the postnatal 4 wks. Group C was treated with nicotine and vitamin C dosed at 1 mg/kg bwt orally for 7 wks, group D was treated with nicotine and sodium selenite dosed at 1 ug/100 g bwt concurrently for 7 wks. The levels of catalase (CAT), superoxide dismutase (SOD), protein carbonyl (PC) and thiobarbituric acid reactive substances (TBARS), were estimated in homogenates of the lung, kidney and liver. Histopathological studies using hematoxylin and eosin as well as immunohistochemical studies using p53 antibody were also done.Results: Nicotine significantly elevated the levels of TBARS and PC as compared to control rats. Groups C and D showed decrease in these levels significantly. CAT and SOD activities of group B were decreased significantly. Significant elevation of CAT and SOD activities was detected in both groups C and D.  Vitamin C elevated the antioxidant enzymes activities to normal levels, however selenium administration improved these levels but still lower than those of group A. Expression of p53 was decreased in group B as compared to group A. Vitamin C completely reversed the expression of p53 as group A.  However, group D did not showed any significant changes in expressions as compared to group B.Conclusion: It is concluded that vitamin C intake was useful than selenium in prevention against nicotine-induced oxidative stress including p53 expression in the lung, kidney and liver of pregnant rats.http://doi.org/10.5455/javar.2016.c168